Treatment of Functional Dyspepsia with a Fixed Peppermint Oil and Caraway Oil Combination Preparation as Compared to Cisapride - Madisch, Ahmed; Heydenreich, Claus-Jürgen; Wieland, Veronika; Hufnagel, Rebecca; Hotz, Jürgen (Arzneimittelforschung, 1999)
The therapeutic equivalence of a fixed combination preparation consisting of peppermint oil and caraway oil (PCC, Enteroplant®) and the prokinetic agent cisapride (CIS, CAS 81098-60-4) was investigated in a four-week randomized controlled double-blind study with planned adaptive interim analysis. The study comprised 120 outpatients with functional dyspepsia. The efficacy was evaluated in 118 patients. Of these, 60 patients received the enteric-coated combination preparation (2 × 1 capsule containing 90 mg peppermint oil + 50 mg caraway oil per day) and 58 patients received the reference preparation cisapride (3 × 10 mg/day).The mean reduction of the pain score (primary variable) recorded on a visual analog scale (VAS) during the four-week treatment was 4.62 points with the peppermint oil/caraway oil preparation. This score was comparable with the mean reduction under cisapride (4.60 points) (p = 0.021; test for equivalence).Equivalence was also found in the secondary variable “frequency of pain” with a reduction by 4.65 points under PCC and by 4.16 points under cisapride carried out on an exploratory basis (p = 0.0034). Comparable results were attained with both treatments in the Dyspeptic Discomfort Score which included the other dyspeptic symptoms as well as intestinal and extra- intestinal autonomic symptoms, in the prognosis as appraised by the physician and in the CGI scales (Clinical Global Impressions). Corresponding results were also found in Helicobacter pylori-positive patients and patients with initially intense epigastric pain in the two treat- ment groups.The combination preparation consisting of peppermint oil and caraway oil appears to be comparable with cisapride and provides an effective means for treatment of functional dyspep- sia. Both medications were tolerated well (adverse events were reported in 12 patients of the PCC group and in 14 patients of the CIS group).
Keywords: Caraway oil; CAS 81098-60-4; Cisapride; Dyspepsia; functional; Enteroplant®, clinical studies; equivalence; Peppermint oil